2016
DOI: 10.1021/acs.est.6b01973
|View full text |Cite
|
Sign up to set email alerts
|

pH and Organic Carbon Dose Rates Control Microbially Driven Bioremediation Efficacy in Alkaline Bauxite Residue

Abstract: Bioremediation of alkaline tailings, based on fermentative microbial metabolisms, is a novel strategy for achieving rapid pH neutralization and thus improving environmental outcomes associated with mining and refining activities. Laboratory-scale bioreactors containing bauxite residue (an alkaline, saline tailings material generated as a byproduct of alumina refining), to which a diverse microbial inoculum was added, were used in this study to identify key factors (pH, salinity, organic carbon supply) controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…Microbial DNA was extracted from frozen samples (0.60 g tailings or soil) with a MoBio PowerSoil DNA Isolation kit, amplified by PCR with the universal Bacteria/Archaea 16S rRNA primers 926F/1392R (V6–V8 region) and sequenced with the Illumina MiSeq platform according to the procedure outlined in Santini et al (2016) . Sequence data were processed using QIIME according to Santini et al (2015b) for quality control through to taxonomy assignment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial DNA was extracted from frozen samples (0.60 g tailings or soil) with a MoBio PowerSoil DNA Isolation kit, amplified by PCR with the universal Bacteria/Archaea 16S rRNA primers 926F/1392R (V6–V8 region) and sequenced with the Illumina MiSeq platform according to the procedure outlined in Santini et al (2016) . Sequence data were processed using QIIME according to Santini et al (2015b) for quality control through to taxonomy assignment.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies to date have focused on the role of vegetation in driving in situ rehabilitation and the establishment of a stable, self-sustaining ecosystem in tailings ( Young et al, 2012 , 2015 ; Ni et al, 2014 , 2015 ), neglecting the role of microbial communities in in situ rehabilitation. Microbial communities can make important contributions to key aspects of tailings rehabilitation including pH neutralization ( Santini et al, 2015a , 2016 ), nutrient accumulation ( Banning et al, 2010 ; Zhan and Sun, 2011 ; Nelson et al, 2015 ; Santini et al, 2015a ; Li et al, 2016 ), degradation of tailings-specific contaminants such as cyanide and thiocyanate ( Skowronski and Strobel, 1969 ; Akcil, 2003 ; Vu et al, 2013 ), and plant-microbe symbioses ( Grandlic et al, 2008 ; Banning et al, 2010 ; Solis-Dominguez et al, 2011 ; Young et al, 2012 ). Enhancing these beneficial contributions is predicated on an improved understanding of the early stages of microbial community assembly and succession in tailings; in particular, the key geochemical and physical controls on microbial recruitment, growth, and community succession.…”
Section: Introductionmentioning
confidence: 99%
“…residue and found that microorganisms can secrete organic acids through glucose metabolism, thereby reducing the pH from 9.5 to 6.5 (Santini et al, 2016). Bulk storage of bauxite residue provides an anaerobic environment for microorganisms, enabling them to metabolize organic acid.…”
Section: Santini Et Al Investigated the Influence Of Microorganisms On The Alkalinity Of Bauxitementioning
confidence: 99%
“…In one study the best results were obtained by adding both a source of organic carbon and a soil inoculum containing microorganisms, and as well as decreasing the pH, the concentrations of As, Mo, V, and Al in solution also decreased, likely via sorption and precipitation (Santini & Peng, 2017). Solid bauxite tailings amended with glucose and microorganisms again demonstrated that stimulating the development of anaerobic and fermentative conditions was an effective remediation strategy (Santini et al, 2016). These results were replicated in scaled up 30 L experiments (Santini et al, 2019).…”
Section: Field and Laboratory Studies Of Bauxite Waste Remediationmentioning
confidence: 99%